Association of hematological indices with neurological symptoms in COVID 19 patients - Zeynep Ünlütürk; Selma Tekin; Hülya Aybek; Çağdaş Erdoğan; Esin Avcı; Tugba Sarı; Secil Deniz; Erhan Ugurlu; Murat Seyit; İsmail Hakkı Akbudak (Cukurova Medical Journal, 2022)
Purpose: The aim of this study was to compare the neurological involvement in Coronavirus 19 (COVID-19) patients with laboratory findings with these cost-free, practical tests. Materials and Methods: Of the 170 patients diagnosed COVID-19, 103 patients could be reached by phone, and neurological symptoms were recorded as three categories. Laboratory tests of the patients and 103 controls whose real-time polymerase chain reaction (RT-PCR) test negative without any chronic disease history and drug use were obtained from the hospital software. Results: White blood cell, neutrophil, lymphocyte, eosinophil, basophil, platelet were lower, monocyte to lymphocyte ratio and platelet to lymphocyte ratio higher in patients than controls. In the group with central nervous system findings, red blood cell and hematocrit counts, in the group with peripheral nervous system findings, lymphocyte and platelet counts and with sleep disturbances and muscle pain group eosinophil counts were lower in patients than those without. Conclusion: COVID-19 patients with neurological symptoms have some hematological abnormalities. The presence of certain hematological findings may be a clue to the emergence of neurological symptoms, and early detection and correction of these hematological abnormalities may be the solution to prevent the development of neurological symptoms in COVID-19.